CODE SWITCHING IN ELECTRONIC STORE CONVERSATIONS: a case study at Electronic City Be-Mall Bandung - Issusanti Ningtyas, - (2007)
The present study examines the realization of code switching in electronic store conversations at Electronic City Bandung. This paper elaborates three major problems. First, it investigates the languages involved in the switching. Second, it discusses the types of code switching. Third, it explores the reasons underlying the use ofcode switching. The present study is largely qualitative. Some quantification, however, is involved to deal with occurrences ofcode switching. The data were gathered through tape recording and interviews. The recorded data were transcribed for identification and classification of code switching. A descriptive-quantitative analysis was employed to examine tendencies in the realization of code switching. Finally, data from the interview were examined to explore reasons behind the use of code switching. . The results show that there were five languages involved in the switching, namely Indonesian, English, Sundanese, Japanese, and Cantonese, and Indonesian appeared to be the base in most contexts. The study also shows that all the three types of code switching proposed by Poplack (i.e. tag, intersentential, and intrasentential switchings) were evidenced in the conversations. Intrasentential switching occurred most frequently and tag switching appeared least Finally, the study finds several reasons for the occurrences of code switching in Electronic City conversations, i.e. expressing technical terms, calling names, and difficulties in finding Indonesian counterparts for English terms.